Estrés laboral y sintomático en el personal administrativo de la Universidad Nacional de Loja - Reyes Suárez, Enrri Roberto (2022)
Occupational and symptomatic stress in workers is a global health problem that ends up damaging physically and emotionally and leads to serious deterioration. The purpose of this study was to identify the levels of work stress, to know the presence of symptomatic stress of Universidad Nacional de Loja administrative staff, according to sex and age group; and to establish the relationship between both variables. A quantitative, prospective, cross-sectional cohort approach was used, in which 149 people who met the inclusion and exclusion criteria participated, made up of 53.7% women and 46.3% men, to whom the work stress questionnaire of the International Labor Organization-World Health Organization and the SEPPO ARO Symptomatic Stress Scale were applied, where it was obtained that 87.2% show a low level of work stress, 8.1% intermediate work stress and 4.7% stress moderate labor. In relation to symptomatic stress, it was known that 38.3% presented symptomatic stress, which was higher in women with 21.5% than in men with 16.8%. There exists a greater association between the presence of symptomatic stress and low level of work stress, with 30.2%. Although there was no statistical significance, it is concluded that in the present investigation the low level of work stress prevails and more frequently in the mature adult age group of both sexes